An Effort to Increase the Independence of Pregnant Women in Detecting High Risk and Complications of Pregnancy - Ika Mardiyanti; Yasi Anggasari (Universitas Muhammadiyah Sidoarjo, 2021)
Health problems for pregnant women, both physically and psychologically, have an impact on the quality of life of the mother and the baby she is carrying. Women with high-risk pregnancies need to prepare themselves with more attention to their health conditions in facing pregnancy. Several factors that influence the independence of pregnant women in early detection of high risk pregnancies include age, developmental conditions, health conditions, cultural orientation, health care systems, family system factors or family support, lifestyle, environmental factors and available resources. The output target to be achieved in the implementation of this community service activity is to increase the understanding and skills of pregnant women about high-risk pregnancies and to be published in national journals. Efforts to increase the independence of pregnant women in detecting high risks and complications of pregnancy through the use of the health of both mother and childbook, Skor Pudji Rochyati and birth planning and complication prevention program stickers are a form of self-awareness for pregnant women and supported by social support by their families, it is hoped that pregnant women will be fully aware of the signs and dangers that occur. on himself and checked himself into a health facility and wanted to be referred to a higher level of service precisely and quickly.